2012
DOI: 10.1103/physrevc.86.024306
|View full text |Cite
|
Sign up to set email alerts
|

Correlations in nuclear matter

Abstract: We analyze the nuclear matter correlation properties in terms of the pair correlation function. To this aim we systematically compare the results for the variational method in the lowest-order constrained variational (LOCV) approximation and for the Bruekner-Hartree-Fock (BHF) scheme. A formal link between the Jastrow correlation factor of LOCV and the defect function (DF) of BHF is established and it is shown under which conditions and approximations the two approaches are equivalent. From the numerical compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 58 publications
3
34
0
Order By: Relevance
“…1 for a review) yield comparable results at densities n < ∼ 2 − 3n 0 , 31-34 there remains considerable disagreement at higher densities. [35][36][37][38][39] This leads to a spread in the predictions of the maximum mass between 1.8M to 2.5M . 31,35,36,40 The high-density part of the EoS of symmetric nuclear matter, at densities between ∼ 2ρ 0 and ∼ 4ρ 0 , can be constrained by studying the flow of matter in heavy-ion collision experiments.…”
Section: Nucleonic Corementioning
confidence: 99%
“…1 for a review) yield comparable results at densities n < ∼ 2 − 3n 0 , 31-34 there remains considerable disagreement at higher densities. [35][36][37][38][39] This leads to a spread in the predictions of the maximum mass between 1.8M to 2.5M . 31,35,36,40 The high-density part of the EoS of symmetric nuclear matter, at densities between ∼ 2ρ 0 and ∼ 4ρ 0 , can be constrained by studying the flow of matter in heavy-ion collision experiments.…”
Section: Nucleonic Corementioning
confidence: 99%
“…The second EOS is the so-called APR EOS by Akmal et al (1998) obtained from the Argonne v 18 NN interaction and a variational procedure as well as Urbana three-nucleon interactions. Although the BHF and variational methods are connected (Baldo & Moshfegh 2012), they give different EOS at high density. We assume that the matter is composed of neutrons, protons, and leptons in betaequilibrium where electrons and muons are treated as relativistic Fermi gas.…”
Section: Equation Of Statementioning
confidence: 99%
“…In the study of nuclear matter, the N N interaction is an important ingredient and a decisive role on the description of the nuclear equations of state of symmetric nuclear and neutron matters, information of which is closely related to the neutron star physics. There are several theories of nuclear matter treating the N N correlations, such as Brueckner-Hartree-Fock (BHF) and Brueckner-Bethe-Goldstone (BBG) [23], Fermi hypernetted chain [24], Green's function Monte Carlo (GFMC) [25,26], auxiliary field diffusion Monte Carlo (AFDMC) [27][28][29], and coupled cluster theory (CC) [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Baldo et al have performed the benchmark calculations of nuclear matter based on these different theories with the same N N interactions [23]. From the results, it is found that these theories provides the similar energies per particle of nuclear matter to each other in case of the short-range correlation, but, there exists a large difference between them for the N N interaction including tensor and LS forces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation